Cloning and sequence analysis of Interleukin (IL)-2, IL-4, IL-10, and IL-18 of Marwari horse - SINGHA, HARISANKAR; GOYAL, SACHIN K; MALIK, PRAVEEN (The Indian Journal of Animal Sciences, 2015)
Cytokines play very important roles in the development of protective immune responses against a variety of pathogens. During the last decade rapid progress has been made in the cloning and characterization of cytokines from livestock and companion animals. However, no such work was carried out on cytokines of Indian horse breed. The present work was undertaken with the objective of generating sequence information of cytokines of Marwari horse. The cDNAs encoding interleukin (IL)-2, IL-4, IL-10 and IL-18 of Marwari horse were cloned, sequenced and subsequently compared with respective interleukin sequences of mammalian species including zebra, donkey, cattle, buffalo, sheep, goat, camel and pig available in GenBank database. Horse IL-10 and IL-18 shows nearly 90% sequence homology both at nucleotide and amino acid level with major livestock species. But horse IL-2 and IL-4 had significant sequence divergence with corresponding interleukins of domestic animals. Structural and functional conservation of horse interleukins in respect of cysteine residues, glycosylation, myristoylation, and phosphorylation motifs revealed that IL-10 and IL-18 molecules are evolutionary conserved across species. Nucleotide and amino acid sequences identity and phylogenetic analyses of the 4 cytokine genes in the present study indicated that horse cytokines are closely related to that of pig and camel cytokines.